Using TPS Via Group Scrabble to Promote Students English Learning Vocabulary - Alimatunnis, Alimatunnis; Samtidar, Samtidar; G., Hasriani (State University of Makassar, 2024)
This study aims to promote students' use of Scrabble game combined with Think-Pair-Share method in engaging English vocabulary learning cooperatively or individually. This research provides benefits and useful information in teaching and learning, especially in vocabulary learning through the promotion of game media. The learning process is responsive to teaching materials using Scrabble game media with Think-Pair-Share technique. This research was conducted using Descriptive Qualitative, for data collection techniques, researcher used observation methods, documentation studies, and also interviews conducted in the school environment. The results of the acquisition of class 1A scores experienced a satisfactory increase starting from cycle II sessions I and II 57.14% - 80.95% while the acquisition of class 1B scores 54.17% - 87.5% the acquisition proved satisfactory results. Promoting the use of Scrabble vocabulary game media as English language learning media and TPS method has a positive influence on students, able to arouse interest in learning, increase students' vocabulary better, help students to learn to engage in the language learning process cooperatively and individually.Keywords: Scrabble game, Think Pair Share, English vocabulary teaching